2019
DOI: 10.1155/2019/8146257
|View full text |Cite
|
Sign up to set email alerts
|

A Th2 Cytokine Profile in Appendicular Lavage Fluid Suggests Allergy as a Possible Etiology for Acute Appendicitis

Abstract: Acute appendicitis is the most frequent surgical abdominal emergency, but its etiology remains poorly understood. Histological examination of the appendix, following its removal due to acute appendicitis, consistently shows features in common with bronchial asthma, suggesting an allergic reaction as a candidate etiologic factor. Here, we propose the concept of appendicular lavage and use it to study the levels of the Th2 cytokines IL-4, IL-5, and IL-9 in patients with a clinical diagnosis of acute appendicitis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 21 publications
3
46
0
Order By: Relevance
“…The hypothesis that cytokines reflect different types of inflammatory responses (Th1/Th17, Th2) which could be used as biomarkers in patients with appendicitis has also been proposed. In a previous study investigating concentrations of Th2 cytokines in appendicular lavage in 41 adults, concentrations of IL-4 were significantly higher in the patients with phlegmonous appendicitis compared to those with normal appendices, but not compared to the patients with gangrenous appendicitis ( 20 ). Associations have been found between Th17-associated cytokines and complicated appendicitis, indicating that the production of these inflammatory mediators can exaggerate the immune response ( 14 ).…”
Section: Discussionmentioning
confidence: 86%
“…The hypothesis that cytokines reflect different types of inflammatory responses (Th1/Th17, Th2) which could be used as biomarkers in patients with appendicitis has also been proposed. In a previous study investigating concentrations of Th2 cytokines in appendicular lavage in 41 adults, concentrations of IL-4 were significantly higher in the patients with phlegmonous appendicitis compared to those with normal appendices, but not compared to the patients with gangrenous appendicitis ( 20 ). Associations have been found between Th17-associated cytokines and complicated appendicitis, indicating that the production of these inflammatory mediators can exaggerate the immune response ( 14 ).…”
Section: Discussionmentioning
confidence: 86%
“…Recent evidences suggest the presence of an allergic reaction in AA [30][31][32]. A clinical study showed that Th2 cytokines, IL-4, IL-5, and IL-9, which are known to be involved in allergic responses, are elevated in phlegmonous AA lavage fluids compared with appendectomy specimens obtained after clinical suspicion of AA not histologically confirmed [30].…”
Section: Discussionmentioning
confidence: 99%
“…These responses produce histological changes that are described as chronic appendicitis, resolving or focal appendicitis. A wide variety of leucocytes may be seen infiltrating the appendix on histology 42–47 . This is UA, which is here seen to be inflammatory.…”
Section: Clinical Patterns Of Appendicitismentioning
confidence: 67%
“…A wide variety of leucocytes may be seen infiltrating the appendix on histology. [42][43][44][45][46][47] This is UA, which is here seen to be inflammatory. Gene expression studies raise the possibility that these patterns may represent viral infection in UA, as opposed to bacterial infection in CA.…”
Section: Clinical Patterns Of Appendicitismentioning
confidence: 74%
See 1 more Smart Citation